Estrategias de comercialización y su incidencia en la productividad del comercial y piladora López del cantón Ventanas provincia de Los Ríos - Bajaña Suarez, Adriana Elizabeth (2015)
Commercial and peeler Lopez has suppliers that are farmers in the area, consumers are to: Corn: poultry companies, Afaba, champion. Rice: final consumer, red Frejol: final consumer, Frejol gandul: for farmers, Soya: the consumer. Purchase daily maize 1000-2000 bushels at harvest time. For Commercial and peeler López their main problems are not having a brand under which to sell their products to all consumers and inefficiency of their marketing processes even though today many media account be they written, visual , radio, internet but the company has not taken to improve its image. Moreover, in recent years...